High ammonia-nitrogen selective polyamide reverse osmosis membrane and preparation method thereof

CN118059678BActive Publication Date: 2026-10-09HARBIN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410333252.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-22
Publication Date
2026-10-09
Estimated Expiration
2044-03-22

AI Technical Summary

Technical Problem

[0005]本发明针对现有商业膜存在的氨氮截留性能差的问题,提出了一种高氨氮选择性聚酰胺反渗透膜及其制备方法

Benefits of technology

[0027](1) The high-performance ammonia nitrogen adsorbent COF-(SO3H)2 embedded inside the polyamide reverse osmosis membrane can selectively bind ammonia nitrogen inside the separation layer through electrostatic interaction and hydrogen bonding. The effective concentration of ammonia nitrogen inside the membrane increases, forming a reverse concentration gradient, which directionally inhibits the subsequent diffusion process of ammonia nitrogen into the membrane, and significantly improves the ammonia nitrogen retention efficiency of the polyamide reverse osmosis membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118059678B_ABST
    Figure CN118059678B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of reverse osmosis membranes, and particularly relates to a high-ammonia-nitrogen-selective polyamide reverse osmosis membrane and a preparation method thereof. The preparation method is performed according to the following steps: step 1, a high-performance ammonia-nitrogen adsorbent COF-(SO3H)2 is synthesized by using a solvothermal method; step 2, a polysulfone-non-woven fabric support layer is prepared by using a nonsolvent-induced phase inversion method; and step 3, a high-ammonia-nitrogen-selective polyamide reverse osmosis membrane is prepared by using an interfacial polymerization method. Through the above method, the problem of poor ammonia-nitrogen interception performance of conventional reverse osmosis membranes is overcome, while maintaining an ideal salt rejection rate, more than 99% of ammonia-nitrogen in a solution can be intercepted, and the water permeation performance is also greatly improved. The application further provides the high-ammonia-nitrogen-selective polyamide reverse osmosis membrane prepared by the above preparation method, and the polyamide reverse osmosis membrane shows a broad application prospect in the fields of high-quality reuse of domestic sewage, efficient recovery of urine ammonia-nitrogen and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of reverse osmosis membrane technology, and particularly relates to a high ammonia nitrogen selective polyamide reverse osmosis membrane and its preparation method. Background Technology

[0002] Water resources are a vital material foundation for human survival and economic development. With rapid economic growth and urbanization, water scarcity is becoming increasingly severe, posing a serious threat to sustainable economic and social development. High-quality resource-based reuse of domestic sewage has become an important window for alleviating the water shortage crisis, and developing a high-quality domestic sewage reuse strategy is a powerful measure to implement the principle of "water conservation and water source development."

[0003] In recent years, the short-process anaerobic-RO coupling process, with reverse osmosis (RO) membranes as its core technology unit, which features low energy consumption and excellent separation performance, is gradually becoming a key technology platform leading the innovation of low-carbon and high-quality reuse treatment of domestic wastewater, thanks to its green and sustainable treatment concept. However, the anaerobic process has limited efficiency in treating nitrogenous pollutants, only converting them into ammonia nitrogen, which is then discharged downstream to the RO end with the effluent.

[0004] It is worth mentioning that ammonia nitrogen mainly exists in the form of free ammonia (NH3) and ammonium ions (NH4). + Ammonia nitrogen is distributed in the aquatic environment in the form of NH4+, and its physicochemical properties, such as hydration radius and polarity, are highly similar to those of water molecules. Furthermore, it can form hydrogen bonds (NH4+…O) with the polyamide separation layer. This makes it difficult for traditional commercial polyamide RO membranes to efficiently and selectively separate ammonia nitrogen, allowing it to enter the permeate side and resulting in significantly excessive ammonia nitrogen levels in the effluent. This not only poses significant risks to aquatic ecosystem safety and human health but also limits the promotion of the aforementioned coupling process in high-quality reuse of domestic wastewater. Therefore, modifying the polyamide separation layer with novel materials is a powerful measure to improve the ammonia nitrogen separation capacity of RO units, and can fundamentally promote the development of high-quality reuse strategies for domestic wastewater. Summary of the Invention

[0005] This invention addresses the problem of poor ammonia nitrogen retention performance in existing commercial membranes by proposing a high ammonia nitrogen selectivity polyamide reverse osmosis membrane and its preparation method.

[0006] A method for preparing a high ammonia nitrogen selective polyamide reverse osmosis membrane is carried out according to the following steps:

[0007] Step 1: Synthesize high-performance ammonia nitrogen adsorbent COF-(SO3H)2 using a solvothermal method.

[0008] Polyamine monomers and aromatic aldehyde monomers were mixed in an organic solvent to obtain a mixed solution and then sonicated. A liquid-phase organic catalyst was added to the mixed solution, mixed well, degassed, and sealed. The mixed solution was heated under constant temperature conditions. After the reaction was completed, the solid was collected, cooled, washed, and dried for later use.

[0009] Step 2: Prepare polysulfone-nonwoven support layer using a solvent-inducible phase inversion method.

[0010] Polysulfone and organic solvent are mixed and heated and stirred to obtain a mixed solution; the mixed solution is filtered and degassed to obtain a casting solution; under constant temperature and humidity conditions, the casting solution is coated onto a nonwoven fabric to obtain a polysulfone-nonwoven fabric support layer.

[0011] Step 3: Prepare a high ammonia nitrogen selective polyamide reverse osmosis membrane using interfacial polymerization, specifically including:

[0012] Step 3-1: Dissolve aromatic diamine monomers in pure water, and then add interfacial polymerization additives and COF-(SO3H)2 to the aqueous solution to obtain an aqueous solution;

[0013] Step 3-2: Dissolve polyacrylamide monomers in alkane organic solvents, and then add COF-(SO3H)2 to obtain an oil phase solution;

[0014] Step 3-3: Immerse the polysulfone-nonwoven support layer prepared in step 2 into the aqueous solution, and then blow away the residual aqueous solution on its surface after taking it out.

[0015] Steps 3-4: Immerse the purged polysulfone-nonwoven support layer in the oil phase solution to allow it to react, remove it and clean the surface to obtain the composite film;

[0016] Step 3-5: Place the composite membrane obtained in step 3-4 in a constant temperature oven for heat treatment to obtain a high ammonia nitrogen selective polyamide reverse osmosis membrane.

[0017] Further, in step 1, the polyamine monomer is one or more of p-phenylenediamine, 2,5-diaminobenzenesulfonic acid and 2,5-diamino-1,4-benzenedisulfonic acid; the aromatic aldehyde monomer is one or two of pyromellitic methyl methacrylate and trialdehyde phloroglucinol; the molar ratio of the polyamine monomer and the aromatic aldehyde monomer is (1-3):1.

[0018] Further, in step 1, the organic solvent is one or more of n-butanol, o-dichlorobenzene, and dioxane; the ratio of the aromatic aldehyde monomer to the organic solvent is (0.1-0.3) mmol:1 mL; the liquid-phase organic catalyst is one or more of formic acid, acetic acid, and propionic acid, with a concentration of 2-6 mol / L; the ratio of the aromatic aldehyde monomer to the liquid-phase organic catalyst is (0.6-1.0) mmol:1 mL.

[0019] Further, in step 1, the temperature of the constant temperature condition is 100℃~150℃; the reaction time is 48h~96h; and the solvent used in the washing process of collecting the solid is one or more of pure water, dimethylacetamide and acetone.

[0020] Further, in step 2, the polysulfone mass percentage concentration in the mixed solution is 10% to 20%; the organic solvent is one or both of N-methylpyrrolidone and N,N-dimethylformamide; and the temperature in the constant temperature heating condition is 50°C to 100°C.

[0021] Furthermore, in step 2, the constant temperature and humidity conditions are specifically: temperature 20℃~30℃, relative humidity 30%~60%, and the gap between the scraper blades for coating the casting liquid needs to be controlled to be 100~300μm.

[0022] Further, in step 3-1, the aromatic diamine monomer is one or more of o-phenylenediamine, m-phenylenediamine, and p-phenylenediamine; the mass percentage concentration of the aromatic diamine monomer in the aqueous solution is 1.0% to 4.0%; the interfacial polymerization additive is one or more of camphor sulfonic acid, triethylamine, sodium dodecyl sulfate, and sodium dodecyl sulfonate; the mass percentage concentrations of camphor sulfonic acid, triethylamine, sodium dodecyl sulfate, and sodium dodecyl sulfonate are 0% to 2.0% respectively; and the mass percentage concentration of COF-(SO3H)2 in the aqueous solution is 0% to 0.10%.

[0023] Further, in step 3-2, the polyacrylamide chloride monomer is one or more of trimesoyl chloride, terephthaloyl chloride, and phthaloyl chloride; the alkane organic solvent is one or more of n-hexane, cyclohexane, and isoparaffinic alkane Isopar-G; the mass percentage concentration of the polyacrylamide chloride monomer in the oil phase solution is 0.05% to 0.30%; and the mass percentage concentration of COF-(SO3H)2 in the oil phase solution is 0.01% to 0.10%.

[0024] Further, in step 3-3, the immersion time of the aqueous phase is 30s to 120s; the purging pressure is 0.5MPa to 1.0MPa; in step 3-4, the immersion reaction time of the oil phase is 30s to 120s; in step 3-5, the composite membrane obtained in step 3-4 is placed in a constant temperature oven for heat treatment, the oven temperature is 50℃ to 100℃, and the heat treatment time is 2min to 15min.

[0025] Based on the same inventive concept, the present invention also provides a high ammonia nitrogen selective polyamide reverse osmosis membrane, which is prepared using the above-described preparation method.

[0026] Compared with existing commercial polyamide reverse osmosis membranes, the present invention has at least the following beneficial technical effects:

[0027] (1) The high-performance ammonia nitrogen adsorbent COF-(SO3H)2 embedded inside the polyamide reverse osmosis membrane can selectively bind ammonia nitrogen inside the separation layer through electrostatic interaction and hydrogen bonding. The effective concentration of ammonia nitrogen inside the membrane increases, forming a reverse concentration gradient, which directionally inhibits the subsequent diffusion process of ammonia nitrogen into the membrane, and significantly improves the ammonia nitrogen retention efficiency of the polyamide reverse osmosis membrane.

[0028] (2) COF-(SO3H)2 contains abundant hydrophilic sulfonic acid groups and internal pores, which can effectively enhance the hydrophilicity and water transport rate of the reverse osmosis membrane. In addition, COF-(SO3H)2 can also regulate the interfacial polymerization process, effectively inhibiting the accumulation of polyamide matrix in the membrane pores of the support layer, and effectively reducing the membrane thickness and mass transfer resistance without affecting the degree of crosslinking. In summary, this novel membrane improves water flux while maintaining ideal separation performance. Attached Figure Description

[0029] Figure 1 This is a flowchart illustrating the preparation process of the high ammonia nitrogen selective reverse osmosis membrane in this invention.

[0030] Figure 2 (a) A scanning electron microscope image of the polyamide reverse osmosis membrane prepared according to the method described in Example 1;

[0031] Figure 2 (b) A scanning electron microscope image of the polyamide reverse osmosis membrane prepared according to the method described in Comparative Example 1. Detailed Implementation

[0032] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments thereof.

[0033] The design concept of this invention is as follows: Covalent organic frameworks (COFs) possess characteristics such as high porosity, tunable pore size, and directional modification. This invention targets and synthesizes a COF material, COF-(SO3H)2, which exhibits good water stability, excellent ammonia nitrogen adsorption performance, and good compatibility with polyamides. This invention uses COF-(SO3H)2 as a dopant to modify polyamide reverse osmosis composite membranes, resulting in a new generation of high ammonia nitrogen selective polyamide reverse osmosis membranes. This novel reverse osmosis membrane maintains an ideal salt rejection rate while significantly improving its ammonia nitrogen rejection performance due to the reverse concentration gradient generated within the membrane. Simultaneously, its water flux is also increased to a certain extent due to the additional transport channels provided by the COF-(SO3H)2 material.

[0034] Specific Implementation Method 1: This invention provides a method for preparing a high ammonia nitrogen selective polyamide reverse osmosis membrane, the preparation flow chart of which is shown below. Figure 1 As shown, the procedure is as follows:

[0035] Step 1: Synthesize high-performance ammonia nitrogen adsorbent COF-(SO3H)2 using a solvothermal method:

[0036] Polyamine monomers and aromatic aldehyde monomers are mixed in an organic solvent in a certain proportion to obtain a mixed solution and then sonicated. A certain amount of liquid organic catalyst is added to the sonicated mixed solution, and after mixing, it is degassed and sealed. The mixed solution is heated under constant temperature conditions. After the reaction is completed, the solid is collected, cooled, washed, and dried for later use.

[0037] Among them, the polyamine monomer is one or more of p-phenylenediamine, 2,5-diaminobenzenesulfonic acid and 2,5-diamino-1,4-benzenedisulfonic acid; the aromatic aldehyde monomer is one or two of pyromellitic methyl methacrylate and trialdehyde phloroglucinol; the molar ratio of polyamine monomer to aromatic aldehyde monomer is (1-3):1; the organic solvent is one or more of n-butanol, o-dichlorobenzene and dioxane; the ratio of aromatic aldehyde monomer to organic solvent is (0.1-0.3) mmol:1mL.

[0038] The liquid-phase organic catalyst is one or more of formic acid, acetic acid, and propionic acid, with a concentration of 2–6 mol / L; the ratio of aromatic aldehyde monomer to liquid-phase organic catalyst is (0.6–1.0) mmol:1 mL.

[0039] The constant temperature conditions are 100℃~150℃, and the reaction time is 48h~96h; the solvent used in the washing process of collecting solids is one or more of pure water, dimethylacetamide, and acetone.

[0040] Step 2: Prepare the polysulfone-nonwoven support layer using a solvent-inducible phase inversion method:

[0041] Polysulfone and an organic solvent are mixed in a certain proportion and heated and stirred under constant temperature until the solute is completely dissolved to obtain a mixed solution. The mixed solution is then filtered and degassed under vacuum to obtain a uniform and transparent casting solution. Under constant temperature and humidity conditions, the casting solution is continuously coated onto a pre-fixed nonwoven fabric using a coating machine, with water as the gel bath, to obtain a polysulfone-nonwoven fabric support layer.

[0042] The polysulfone mass percentage concentration in the mixed solution is 10%–20%; the organic solvent is one or both of N-methylpyrrolidone and N,N-dimethylformamide; the temperature is 50℃–100℃ under constant temperature heating conditions; the temperature is 20℃–30℃ and the relative humidity is 30%–60% under constant temperature and humidity conditions; the gap between the doctor blades for casting liquid coating needs to be controlled at 100–300 μm.

[0043] Step 3: Prepare a high ammonia nitrogen selective polyamide reverse osmosis membrane using interfacial polymerization:

[0044] Step 3-1: Dissolve aromatic diamine monomers in pure water, then add interfacial polymerization additives and COF-(SO3H)2 to the aqueous solution, stir until homogeneous, and obtain an aqueous solution.

[0045] Step 3-2: Dissolve the polyacrylamide monomer in an alkane organic solvent, then add a certain amount of COF-(SO3H)2, and sonicate to obtain an oil phase solution.

[0046] Step 3-3: Immerse the polysulfone-nonwoven support layer prepared in step 2 into the aqueous solution, and then remove it and evenly blow away the residual aqueous solution on its surface.

[0047] Steps 3-4: Immerse the purged polysulfone-nonwoven support layer in the oil phase solution to allow it to react, then remove it and clean the surface evenly to obtain the composite film.

[0048] Steps 3-5: After the residual n-hexane has naturally evaporated, place the composite membrane obtained in step 3-4 in a constant temperature oven for heat treatment. After taking it out, a high ammonia nitrogen selective polyamide reverse osmosis membrane is obtained.

[0049] The aromatic diamine monomers are one or more of o-phenylenediamine, m-phenylenediamine, and p-phenylenediamine; the mass percentage concentration of the aromatic diamine monomers in the aqueous solution is 1.0% to 4.0%; the interfacial polymerization additives are one or more of camphor sulfonic acid, triethylamine, sodium dodecyl sulfate, and sodium dodecyl sulfonate; the mass percentage concentrations of camphor sulfonic acid, triethylamine, sodium dodecyl sulfate, and sodium dodecyl sulfonate are 0% to 2.0% respectively; and the mass percentage concentration of COF-(SO3H)2 in the aqueous solution is 0% to 0.10%.

[0050] The polyacrylamide chloride monomer is one or more of trimesoyl chloride, terephthaloyl chloride, and phthaloyl chloride; the alkane organic solvent is one or more of n-hexane, cyclohexane, and isoparaffin Isopar-G; the mass percentage concentration of the polyacrylamide chloride monomer in the oil phase solution is 0.05% to 0.30%; the mass percentage concentration of COF-(SO3H)2 in the oil phase solution is 0.01% to 0.10%.

[0051] The immersion time in the aqueous phase is 30s to 120s; the purging pressure is 0.5MPa to 1.0MPa, and nitrogen or argon is used as the purging gas; the immersion reaction time in the oil phase is 30s to 120s.

[0052] The oven temperature is maintained at 50℃~100℃; the heat treatment time is 2min~15min.

[0053] Specific Implementation Method 2: The present invention also provides a high ammonia nitrogen selective polyamide reverse osmosis membrane, which is prepared using the above preparation method.

[0054] The present invention will be further illustrated and verified by the following comparative examples and embodiments.

[0055] Comparative Example 1:

[0056] A reverse osmosis membrane comprising a polysulfone-nonwoven support layer and a polyamide separation layer, prepared using conventional techniques;

[0057] Polysulfone was dissolved in the organic solvent N-methylpyrrolidone, and its mass percentage concentration was controlled at 16%. A polysulfone-nonwoven support layer was prepared by a solvent-induced phase inversion method, wherein the constant temperature heating temperature was 60℃; the constant temperature and humidity conditions were 25℃ and 40%; and the doctor blade gap was controlled at 200μm during the casting liquid coating process.

[0058] m-Phenylenediamine was dissolved in pure water to obtain an aqueous solution of m-Phenylenediamine with a mass percentage concentration of 2.0% (without any additives).

[0059] Tristyroyl chloride was dissolved in n-hexane to obtain a 0.1% (w / w) oil phase solution of tristyroyl chloride.

[0060] The support layer was immersed in the above aqueous solution for 60 seconds, then removed and the surface was cleaned with nitrogen gas (pressure 0.8 MPa).

[0061] The support layer, after being soaked in the aqueous phase, was immersed in the oil phase solution for 60 seconds, rinsed with n-hexane to terminate the reaction, and after natural evaporation, placed in an oven for heat treatment at 60°C for 5 minutes.

[0062] Test conditions: The pure water flux of the membrane was tested under the conditions of pressure 1.0 MPa, temperature 25℃, and pH 7.0. Then, the salt rejection rate and ammonia nitrogen rejection efficiency of the membrane were tested using 2000 mg / L sodium chloride solution and 50 mg N / L ammonium chloride solution, respectively. Under the same preparation conditions, at least three sets of parallel experiments were carried out, and the average value of the experimental results was taken to improve the accuracy and reliability of the experimental data. The test data are recorded in Table 1.

[0063] Example 1:

[0064] The differences from Comparative Example 1 lie in the composition of the aqueous solution, the composition of the oil solution, and the heat treatment time. The specific changes are as follows:

[0065] First, a high-performance ammonia nitrogen adsorbent COF-(SO3H)2 was prepared by a solvothermal method: 3 mmol of 2,5-diamino-1,4-benzenedisulfonic acid and 2 mmol of trialdehyde phloroglucinol were mixed in 30 mL of dioxane and sonicated. Then, 5 mL of acetic acid, a liquid organic catalyst with a concentration of 3 mol / L, was added. After mixing, degassing, and sealing, the mixture was heated at a constant temperature of 120 °C for 72 h. The solid was collected, washed successively with pure water, dimethylacetamide, and acetone, and then dried for later use.

[0066] Triethylamine (1.0%), camphor sulfonic acid (1.5%), and sodium dodecyl sulfate (1.0%) were added to a 2.0% m-phenylenediamine aqueous solution and stirred until homogeneous to obtain an aqueous solution.

[0067] Add 0.01% COF-(SO3H)2 to a 0.1% pyromellitic methyl chloride oil phase solution, and then ultrasonically vibrate to disperse it evenly to obtain an oil phase solution;

[0068] Heat treatment for 10 minutes.

[0069] The test method used in Comparative Example 1 was adopted, and the test data is recorded in Table 1.

[0070] Example 2:

[0071] The differences from Comparative Example 1 lie in the composition of the aqueous solution, the composition of the oil solution, and the heat treatment time. The specific changes are as follows:

[0072] High-performance ammonia nitrogen adsorbent COF-(SO3H)2 was prepared according to the solvothermal method in Example 1.

[0073] Triethylamine (1.0%), camphor sulfonic acid (1.5%), and sodium dodecyl sulfate (1.0%) were added to a 2.0% m-phenylenediamine aqueous solution and stirred until homogeneous to obtain an aqueous solution.

[0074] Add 0.02% COF-(SO3H)2 to a 0.1% (w / w) pyromellitic methyl chloride oil phase solution, and then ultrasonically vibrate to disperse it evenly to obtain an oil phase solution;

[0075] Heat treatment for 10 minutes.

[0076] The test method used in Comparative Example 1 was adopted, and the test data is recorded in Table 1.

[0077] Example 3:

[0078] The differences from Comparative Example 1 lie in the composition of the aqueous solution, the composition of the oil solution, and the heat treatment time. The specific changes are as follows:

[0079] High-performance ammonia nitrogen adsorbent COF-(SO3H)2 was prepared according to the solvothermal method in Example 1.

[0080] Triethylamine (1.0%), camphor sulfonic acid (1.5%), and sodium dodecyl sulfate (1.0%) were added to a 2.0% m-phenylenediamine aqueous solution and stirred until homogeneous to obtain an aqueous solution.

[0081] Add 0.04% COF-(SO3H)2 to a 0.1% pyromellitic methyl chloride oil phase solution, and then ultrasonically vibrate to disperse it evenly to obtain an oil phase solution;

[0082] Heat treatment for 10 minutes.

[0083] The test method used in Comparative Example 1 was adopted, and the test data is recorded in Table 1.

[0084] Example 4:

[0085] The difference from Comparative Example 1 lies in the composition of the oil phase solution. The specific changes are as follows:

[0086] High-performance ammonia nitrogen adsorbent COF-(SO3H)2 was prepared according to the solvothermal method in Example 1.

[0087] Add 0.01% COF-(SO3H)2 to a 0.1% pyromellitic methyl chloride oil phase solution, and then ultrasonically vibrate to disperse it evenly to obtain an oil phase solution;

[0088] The test method used in Comparative Example 1 was adopted, and the test data is recorded in Table 1.

[0089] Example 5:

[0090] The difference from Comparative Example 1 lies in the composition of the oil phase solution. The specific changes are as follows:

[0091] High-performance ammonia nitrogen adsorbent COF-(SO3H)2 was prepared according to the solvothermal method in Example 1.

[0092] Add 0.02% COF-(SO3H)2 to a 0.1% (w / w) pyromellitic methyl chloride oil phase solution, and then ultrasonically vibrate to disperse it evenly to obtain an oil phase solution;

[0093] The test method used in Comparative Example 1 was adopted, and the test data is recorded in Table 1.

[0094] Example 6:

[0095] The differences from Comparative Example 1 lie in the composition of the aqueous solution, the composition of the oil solution, and the heat treatment time. The specific changes are as follows:

[0096] High-performance ammonia nitrogen adsorbent COF-(SO3H)2 was prepared according to the solvothermal method in Example 1.

[0097] Triethylamine (1.0%), camphor sulfonic acid (1.5%), sodium dodecyl sulfate (1.0%), and 0.01% COF-(SO3H)2 were added to a 2.0% m-phenylenediamine aqueous solution and stirred until homogeneous to obtain an aqueous solution.

[0098] Add 0.01% COF-(SO3H)2 to a 0.1% pyromellitic methyl chloride oil phase solution, and then ultrasonically vibrate to disperse it evenly to obtain an oil phase solution;

[0099] Heat treatment for 10 minutes.

[0100] The test method used in Comparative Example 1 was adopted, and the test data is recorded in Table 1.

[0101] Example 7:

[0102] The differences from Comparative Example 1 lie in the composition of the aqueous solution, the composition of the oil solution, and the heat treatment time. The specific changes are as follows:

[0103] High-performance ammonia nitrogen adsorbent COF-(SO3H)2 was prepared according to the solvothermal method in Example 1.

[0104] Triethylamine (1.0%), camphor sulfonic acid (1.5%), and sodium dodecyl sulfate (1.0%) were added to a 2.0% p-phenylenediamine aqueous solution and stirred until homogeneous to obtain an aqueous solution.

[0105] Add 0.02% COF-(SO3H)2 to a 0.1% (w / w) pyromellitic methyl chloride oil phase solution, and then ultrasonically vibrate to disperse it evenly to obtain an oil phase solution;

[0106] Heat treatment for 10 minutes.

[0107] The test method used in Comparative Example 1 was adopted, and the test data is recorded in Table 1.

[0108] Example 8:

[0109] The differences from Comparative Example 1 lie in the composition of the aqueous solution, the composition of the oil solution, and the heat treatment time. The specific changes are as follows:

[0110] High-performance ammonia nitrogen adsorbent COF-(SO3H)2 was prepared according to the solvothermal method in Example 1.

[0111] Triethylamine (1.0%), camphor sulfonic acid (1.5%), and sodium dodecyl sulfate (1.0%) were added to a 2.0% m-phenylenediamine aqueous solution and stirred until homogeneous to obtain an aqueous solution.

[0112] Trimethylbenzene chloride was dissolved in isoparaffin Isopar-G to obtain a 0.1% (w / w) trimethylbenzene chloride solution. 0.02% COF-(SO3H)2 was added to the above solution and ultrasonically vibrated to disperse it evenly, thus obtaining an oil phase solution.

[0113] Heat treatment for 10 minutes.

[0114] The test method used in Comparative Example 1 was adopted, and the test data is recorded in Table 1.

[0115] Example 9:

[0116] The differences from Comparative Example 1 lie in the composition of the oil phase solution and the heat treatment time. The specific changes are as follows:

[0117] High-performance ammonia nitrogen adsorbent COF-(SO3H)2 was prepared according to the solvothermal method in Example 1.

[0118] Add 0.02% COF-(SO3H)2 to a 0.1% (w / w) pyromellitic methyl chloride oil phase solution, and then ultrasonically vibrate to disperse it evenly to obtain an oil phase solution;

[0119] Heat treatment for 10 minutes.

[0120] The test method used in Comparative Example 1 was adopted, and the test data is recorded in Table 1.

[0121] Effect verification:

[0122] Table 1. Performance Comparison of Polyamide Reverse Osmosis Membranes Prepared in Comparative Examples and Examples

[0123] Comparative Example 1 18.37 97.39 93.74 Example 1 35.97 99.54 98.96 Example 2 41.29 99.57 99.57 Example 3 37.34 99.51 99.10 Example 4 24.56 98.76 97.24 Example 5 28.69 98.59 98.35 Example 6 38.14 99.47 99.15 Example 7 27.03 98.16 96.13 Example 8 31.17 97.61 96.36 Example 9 23.64 97.21 95.75

[0124] As can be seen from the data in Table 1, adding an appropriate concentration of COF-(SO3H)2 material to the polyamide separation layer can significantly improve the ammonia nitrogen rejection efficiency and pure water flux while maintaining the ideal salt rejection rate. Among them, adding COF-(SO3H)2 to the oil phase solution has a better effect. In addition, adding an appropriate amount of interfacial polymerization additive to the aqueous phase solution is beneficial to obtaining a modified polyamide reverse osmosis membrane with better overall performance.

[0125] Figure 2 (a) and Figure 2(b) are scanning electron microscope images of the polyamide reverse osmosis membranes prepared according to the preparation methods of Example 1 and Comparative Example 1, respectively. As shown in the figure, the addition of COF-(SO3H)2 in Example 1 helps to regulate the interfacial polymerization reaction, making the reverse osmosis membrane surface intact and exhibiting a more uniform ridge-valley structure. This not only increases the effective filtration area of ​​the membrane but also maintains a good degree of crosslinking, thereby improving the rejection efficiency and pure water flux of the obtained reverse osmosis membrane. In contrast, the reverse osmosis membrane obtained in Comparative Example 1 has a large number of nodules on its surface, which are unevenly distributed and have certain defects, resulting in poor separation performance.

[0126] In summary, the high ammonia nitrogen selective polyamide reverse osmosis membrane prepared by this invention has excellent ammonia nitrogen separation performance and water transport rate, and shows broad application prospects in the fields of high-quality reuse of domestic sewage and efficient recovery of ammonia nitrogen from urine.

[0127] The applicant declares that this invention illustrates the high ammonia nitrogen selective polyamide reverse osmosis membrane and its preparation method through the above embodiments. However, the application of this invention is not limited to the above examples. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims. Furthermore, this invention is not limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a high ammonia nitrogen selective polyamide reverse osmosis membrane, characterized in that: Follow these steps: Step 1: Synthesize high-performance ammonia nitrogen adsorbent using a solvothermal method. : Polyamine monomers and aromatic aldehyde monomers were mixed in an organic solvent to obtain a mixed solution and then sonicated. A liquid-phase organic catalyst was added to the mixed solution, mixed well, degassed, and sealed. The mixed solution was heated under constant temperature conditions. After the reaction was completed, the solid was collected, cooled, washed, and dried for later use. The polyamine monomer is 2,5-diamino-1,4-benzenedisulfonic acid; the aromatic aldehyde monomer is trialdehyde phloroglucinol; the molar ratio of the polyamine monomer to the aromatic aldehyde monomer is (1-3):1; Step 2: Prepare the polysulfone-nonwoven support layer using a solvent-inducible phase inversion method: Polysulfone and organic solvent are mixed and heated and stirred under constant temperature to obtain a mixed solution; the mixed solution is filtered and degassed to obtain a casting solution; under constant temperature and humidity conditions, the casting solution is coated onto a nonwoven fabric to obtain a polysulfone-nonwoven fabric support layer. Step 3: Prepare a high ammonia nitrogen selective polyamide reverse osmosis membrane using interfacial polymerization, specifically including: Step 3-1: Dissolve the aromatic diamine monomer in pure water, and then add the interfacial polymerization additive to the aqueous solution. An aqueous solution is obtained; the interfacial polymerization additive is one or more of camphor sulfonic acid, triethylamine, sodium dodecyl sulfate, and sodium dodecyl sulfonate; Step 3-2: Dissolve the polyacrylamide monomer in an alkane organic solvent, and then add it to the solvent. An oil phase solution was obtained; Step 3-3: Immerse the polysulfone-nonwoven support layer prepared in step 2 into the aqueous solution, and then blow away the residual aqueous solution on its surface after taking it out. Steps 3-4: Immerse the purged polysulfone-nonwoven support layer in the oil phase solution to allow it to react, remove it and clean the surface to obtain the composite film; Step 3-5: Place the composite membrane obtained in step 3-4 in a constant temperature oven for heat treatment to obtain a high ammonia nitrogen selective polyamide reverse osmosis membrane.

2. The method for preparing a high ammonia nitrogen selective polyamide reverse osmosis membrane according to claim 1, characterized in that, In step 1, the organic solvent is one or more of n-butanol, o-dichlorobenzene, and dioxane; the ratio of the aromatic aldehyde monomer to the organic solvent is (0.1-0.3) mmol: 1 mL; the liquid-phase organic catalyst is one or more of formic acid, acetic acid, and propionic acid, with a concentration of 2-6 mol / L; the ratio of the aromatic aldehyde monomer to the liquid-phase organic catalyst is (0.6-1.0) mmol: 1 mL.

3. The method for preparing a high ammonia nitrogen selective polyamide reverse osmosis membrane according to claim 1, characterized in that, In step 1, the constant temperature is 100℃~150℃; the reaction time is 48h~96h; and the solvent used in the washing process of collecting the solid is one or more of pure water, dimethylacetamide and acetone.

4. The method for preparing a high ammonia nitrogen selective polyamide reverse osmosis membrane according to claim 1, characterized in that, In step 2, the polysulfone mass percentage concentration in the mixed solution is 10% to 20%; the organic solvent is one or both of N-methylpyrrolidone and N,N-dimethylformamide; and the temperature in the constant temperature heating condition is 50℃ to 100℃.

5. The method for preparing a high ammonia nitrogen selective polyamide reverse osmosis membrane according to claim 1, characterized in that, In step 2, the constant temperature and humidity conditions are specifically: temperature 20℃~30℃, relative humidity 30%~60%; the gap between the scraper blades for the casting liquid coating needs to be controlled to be 100~300 μm.

6. The method for preparing a high ammonia nitrogen selective polyamide reverse osmosis membrane according to claim 1, characterized in that, In step 3-1, the aromatic diamine monomer is one or more of o-phenylenediamine, m-phenylenediamine, and p-phenylenediamine; the mass percentage concentration of the aromatic diamine monomer in the aqueous solution is 1.0% to 4.0%; the mass percentage concentrations of camphor sulfonic acid, triethylamine, sodium dodecyl sulfate, and sodium dodecyl sulfonate are 0% to 2.0% respectively; the mass percentage concentration of the aromatic diamine monomer in the aqueous solution is 1.0% to 4.0%; the mass percentage concentration of camphor sulfonic acid, triethylamine, sodium dodecyl sulfate, and sodium dodecyl sulfonate in the aqueous solution is 0% to 2.0%; The mass percentage concentration is 0.01% to 0.10%.

7. The method for preparing a high ammonia nitrogen selective polyamide reverse osmosis membrane according to claim 1, characterized in that, In step 3-2, the polyacrylamide chloride monomer is one or more of trimesoyl chloride, terephthaloyl chloride, and phthaloyl chloride; the alkane organic solvent is n-hexane, cyclohexane, or isoalkanes. One or more of the following; the mass percentage concentration of the polyacrylamide chloride monomer in the oil phase solution is 0.05% to 0.30%; the oil phase solution contains The mass percentage concentration is 0.01% to 0.10%.

8. The method for preparing a high ammonia nitrogen selective polyamide reverse osmosis membrane according to claim 1, characterized in that, In step 3-3, the immersion time of the aqueous phase is 30 s to 120 s; the purging pressure is 0.5 MPa to 1.0 MPa; in step 3-4, the immersion reaction time of the oil phase is 30 s to 120 s; in step 3-5, the composite membrane obtained in step 3-4 is placed in a constant temperature oven for heat treatment, the oven temperature is 50℃ to 100℃, and the heat treatment time is 2 min to 15 min.

9. A high ammonia nitrogen selective polyamide reverse osmosis membrane, characterized in that, It is prepared using the preparation method described in any one of claims 1-8.

Citation Information

Patent Citations

  • Covalent organic framework material containing sulfonic acid groups as well as preparation and application of covalent organic framework material

    CN112679731A

  • Covalent organic framework doped polyamide reverse osmosis membrane and preparation method thereof

    CN114618331A